2015
DOI: 10.1111/lam.12514
|View full text |Cite
|
Sign up to set email alerts
|

High temperature alcoholic fermentation of orange peel by the newly isolated thermotolerant Pichia kudriavzevii KVMP10

Abstract: Citrus peel waste is one of the most underutilized and geographically diverse residues in the planet. In attempt to develop a citrus peel based biorefinery we report here the isolation of a yeast which exhibited favourable technological characteristics for the production of ethanol through utilization of the specific food waste. Pichia kudriavzevii KVMP10 was highly thermotolerant and utilized both hexoses and pentoses for ethanol production, which was achieved at elevated rates, highlighting its great potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…kudriavzevii in 1965 (Kurtzman et al 2008 ). Several I. orientalis strains produce ethanol and have higher thermotolerance, salt tolerance, and acid tolerance than S. cerevisiae (Isono et al 2012 ; Koutinas et al 2016 ). Because of its resistance to multiple stress factors, I. orientalis has potential application in bioethanol production and succinic acid production (Kitagawa et al 2010 ; Kwon et al 2011 ; Xiao et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…kudriavzevii in 1965 (Kurtzman et al 2008 ). Several I. orientalis strains produce ethanol and have higher thermotolerance, salt tolerance, and acid tolerance than S. cerevisiae (Isono et al 2012 ; Koutinas et al 2016 ). Because of its resistance to multiple stress factors, I. orientalis has potential application in bioethanol production and succinic acid production (Kitagawa et al 2010 ; Kwon et al 2011 ; Xiao et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…boulardii was observed in ulcerative colitis and also in Crohn's disease (Guslandi et al ., ). Several studies on Pichia kudriavzevii have demonstrated the technological advantages of the strain for the production of sustainable bioenergy (Koutinas et al ., ; Yuangsaard et al ., ). Also, it has been found in olive fermentation (Golomb et al ., ) and pickled wax gourd (Wu et al ., ) as indigenous microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol production at high temperatures by thermotolerant yeasts has earned much interest due to several advantages as described above [38]. There are several ethanologenic yeasts that have been characterized and classified as thermotolerant yeasts such as K. marxianus [31,37,47], P. kudriavzevii (formally known as I. orientalis) [20,48,49,65,66], Hansenula polymorpha [67], and some strains of S. cerevisiae [21,52,[68][69][70]. However, for cost-effective and efficient ethanol production, not only thermotolerance but also a broad spectrum in sugar assimilation and fermentation capability is beneficial for the conversion of a variety of raw materials containing various sugars to ethanol, especially xylose, which is the most common pentose sugar and the second most abundant after glucose in lignocellulosic biomass and algal biomass [71,72].…”
Section: Utilization Of Various Sugars In Thermotolerant Yeastsmentioning
confidence: 99%
“…The strain produced 78.6 g/L ethanol from 180 g/L glucose at 40°C [20]. The strain KVMP10 that was isolated from soil located beneath apple trees for ethanol production from orange peel achieved 54 g/L ethanol at 42°C [48]. Strain RZ8-1 that was recently isolated from various samples collected from plant orchards in Thailand produced 33.8 g/L ethanol from 160 g/L glucose at 40°C [49].…”
mentioning
confidence: 99%